Tumour heterogeneity and intercellular networks of nasopharyngeal carcinoma at single cell resolution - Liu, Yang; He, Shuai; Wang, Xi-Liang; Peng, Wan; Chen, Qiu-Yan; Chi, Dong-Mei; Chen, Jie-Rong; Han, Bo-Wei; Lin, Guo-Wang; Li, Yi-Qi; Wang, Qian-Yu; Peng, Rou-Jun; et al. (Nature communications, 2021)
The heterogeneous nature of tumour microenvironment (TME) underlying diverse treatment responses remains unclear in nasopharyngeal carcinoma (NPC). Here, we profile 176,447 cells from 10 NPC tumour-blood pairs, using single-cell transcriptome coupled with T cell receptor sequencing. Our analyses reveal 53 cell subtypes, including tumour-infiltrating CD8 + T, regulatory T (Treg), and dendritic cells (DCs), as well as malignant cells with different Epstein-Barr virus infection status. Trajectory analyses reveal exhausted CD8 + T and immune-suppressive TNFRSF4 + Treg cells in tumours might derive from peripheral CX3CR1 + CD8 + T and naïve Treg cells, respectively. Moreover, we identify immune-regulatory and tolerogenic LAMP3 + DCs. Noteworthily, we observe intensive inter-cell interactions among LAMP3 + DCs, Treg, exhausted CD8 + T, and malignant cells, suggesting potential cross-talks to foster an immune-suppressive niche for the TME. Collectively, our study uncovers the heterogeneity and interacting molecules of the TME in NPC at single-cell resolution, which provide insights into the mechanisms underlying NPC progression and the development of precise therapies for NPC. Nasopharyngeal carcinoma is a diverse cancer characterised by a heterogeneous microenvironment. Here, the authors use single cell sequencing to analyse the tumour microenvironment in 10 nasopharyngeal carcinoma tumours and identify different cell types including immune-suppressive T regulatory, tolerogenic dendritic, and exhausted CD8 T cells.